2006
DOI: 10.1161/circulationaha.106.634469
|View full text |Cite|
|
Sign up to set email alerts
|

α-E-Catenin Inactivation Disrupts the Cardiomyocyte Adherens Junction, Resulting in Cardiomyopathy and Susceptibility to Wall Rupture

Abstract: Background-␣-E-catenin is a cell adhesion protein, located within the adherens junction, thought to be essential in directly linking the cadherin-based adhesion complex to the actin cytoskeleton. Although ␣-E-catenin is expressed in the adherens junction of the cardiomyocyte intercalated disc, and perturbations in its expression are observed in models of dilated cardiomyopathy, its role in the myocardium remains unknown. Methods and Results-To determine the effects of ␣-E-catenin on cardiomyocyte ultrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 42 publications
5
96
0
1
Order By: Relevance
“…In vitro, ␣N-and ␣T-catenin can substitute for the adhesive functions f ␣E-catenin, but their restricted expression patterns indicate additional isoform-specific or synergistic functions. This hypothesis was recently confirmed by the inability of endogenous ␣T-catenin expression to rescue heart-specific ␣E-catenin knockout in mice (Sheikh et al, 2006). Ablation of ␣E-catenin expression leads to defects in cardiomyocyte structural integrity; this results in unique forms of cardiomyopathy and susceptibility of the heart wall to rupture after cardiac stress.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In vitro, ␣N-and ␣T-catenin can substitute for the adhesive functions f ␣E-catenin, but their restricted expression patterns indicate additional isoform-specific or synergistic functions. This hypothesis was recently confirmed by the inability of endogenous ␣T-catenin expression to rescue heart-specific ␣E-catenin knockout in mice (Sheikh et al, 2006). Ablation of ␣E-catenin expression leads to defects in cardiomyocyte structural integrity; this results in unique forms of cardiomyopathy and susceptibility of the heart wall to rupture after cardiac stress.…”
Section: Introductionmentioning
confidence: 89%
“…To mediate the normal cell-cell interaction between cardiomyocytes, which is indispensable for cardiac functionality, these three different junctional complexes must be properly organized in the intercalated discs. Knockout experiments revealed that absence of adherens junctions (Linask et al, 1997;Olson et al, 2002;Kostetskii et al, 2005;Sheikh et al, 2006) or desmosomes (Bierkamp et al, 1996;Ruiz et al, 1996;Grossmann et al, 2004) has devastating consequences for heart development and viability. Moreover, mutations in structural proteins that are involved in the organization of the intercalated disc often lead to cardiomyopathy and heart failure (Maeda et al, 1997;McKoy et al, 2000;Norgett et al, 2000;Ferreira-Cornwell et al, 2002;Gerull et al, 2004;Prakasa and Calkins, 2005;Awad et al, 2006a;Awad et al, 2006b;Heuser et al, 2006;Pilichou et al, 2006;Uzumcu et al, 2006;Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial cells, the actin-binding region of α-catenin is also required for VE-cadherin stabilization and accumulation to cortical actin bundles (55). PAs were disrupted in cardiac-specific α-catenin conditional knockout mice, resulting in cardiomyopathy and susceptibility to wall rupture (56).…”
Section: Actin-binding Ability Of -Cateninmentioning
confidence: 99%
“…Although many of their suggested signaling roles originate from studies in non-cardiac cells, it is presumed that catenins may have similar regulatory activities at the ID of cardiomyocytes. In support of this, transgenic mice lacking either -or -catenin result in detrimental effects on the longevity of the animals, with phenotypes ranging from embryonic lethality to the development of early onset DCM (Haegel et al, 1995;Piven et al, 2011;Sheikh et al, 2006). Future studies are necessary to continue addressing this question.…”
Section: Proteins Of the Catenin Familymentioning
confidence: 99%